Investigando o uso do extreme programming como uma metodologia de ensino para aplicações práticas da robótica educacional - Bezerra Júnior, José Etiene (2018)
In an empirical way, it can be seen that technologies applied to education are increasingly present in educational institutions, especially the presence of educational robotics. Educational robotics consists of an educational technology that proposes to make the teaching and learning process more effective, using theoretical knowledge that is applied in practice. One of the major reasons for the presence of robotics is its advantage of being able to work in any area, making use of the interdisciplinary approach. It has been used by several professional in the educational area, as a teaching tool aimed at solving low school performance and avoidance. But for this, it is necessary to carry out a complete planning with the methodology to be followed. In this context, the objective of this paper is to propose a development of educational robotics combined with software engineering, in this case using agile software methodology as a teaching tool for the development of robotics. In this way, analyzes were performed in both robotics and agile methodology, based on this, it was identified that the most appropriate methodology for application of this development is Extreme Programming (XP). Based on this, the methodology developed was applied in a public school with first year students of high school. Thus, to validate this development of XP, two case studies were elaborated. After the accomplishment of this work, it was verified that it is possible to use XP as a teaching methodology for robotics producing results such as: the development of logical reasoning and the development of computational thinking